REFRAMING COMMUNITY EMPOWERMENT: A CRITICAL READING OF PLACE-BASED APPROACH TO PRODAMAS IN KEDIRI, INDONESIA - Tauran, T. (Natapraja, 2025)
This study aims to critique the community empowerment program (Prodamas) in Kediri City, Indonesia. Using Carol Bacchi’s What’s the Problem Represented to Be? (WPR) analytical framework, this study explores how the problem of community empowerment is represented in policy documents, as well as how these representations are produced, disseminated, and maintained. This study employs an interpretive qualitative method, utilizing data sources that include local government regulations, case study reports, and the results of semi-structured interviews with residents. The results shows that Prodamas portrays the community as a passive entity that requires motivation to participate, while structural dimensions such as social inequality, local power relations, and limited citizen capacity are not addressed in the policy. This representation produces discursive and institutional effects that strengthen bureaucratic dominance, reduce the meaning of empowerment to procedural activities, and limit citizen agency. This article makes a theoretical contribution by offering a critical analysis of community empowerment programs in the context of developing countries. This article also encourages a shift in the empowerment approach from mere administrative participation to the formation of a more equitable and reflective political space for citizens at the local level.